Effect of post-injection strategy on greenhouse gas emissions of natural gas/diesel dual-fuel engine at high load conditions. (15th April 2021) - Yousefi, Amin; Guo, Hongsheng; Birouk, Madjid; Liko, Brian; Lafrance, Simon
Highlight: Effect of post-injection on NDDF engine was investigated at high load conditions. Pre-main-post injection can achieve similar or higher ITE than single injection. Pre-main-post injection decreases unburned methane at high load conditions. Pre-main-post injection strategy can reduce GHG and NOx by 10% and 47%. Abstract: In this study the effect of two diesel injection strategies named main-post and pre-main-post on natural gas/diesel dual-fuel (NDDF) combustion at high load conditions is investigated. In the main-post diesel injection strategy, part of diesel is injected after the main injection in the late expansion stroke (post-injection). In the pre-main-post injection strategy, part of diesel fuel is injected before main injection in the early compression stroke (pre-injection) and part of diesel fuel is injected after main injection in the late expansion stroke. The results revealed that the main-post diesel injection strategy did not change the start of combustion compared to single injection strategy. However, the pre-main-post injection strategy significantly increased the cylinder pressure and advanced the start of combustion. The maximum measured indicated fuel efficiencies (IFE) of NDDF engine with both single and pre-main diesel injection strategies were 41.50%. The main-post diesel injection strategy slightly decreased IFE of NDDF (i.e., 40.35%). However, an optimized combustion phasing and pre-main-post injection strategy made it possible to achieve similar or higher IFE than single injection strategy. Moreover, the pre-main-post diesel injection strategy significantly decreased unburned methane emissions. The lowest measured unburned methane emissions when using pre-main-post diesel injection was 0.37 g/kW.h, which was lower than that of single injection (0.80 g/kW.h). Compared to single diesel injection, optimized combustion phasing along with pre-main-post injection strategy reduced GHG and NOx emissions by 10% and 47%, respectively.